Transforming data into insight: Establishment of a pharmacy analytics and outcomes team. (15th December 2020) - Vest, Mary-Haston; Colmenares, Evan W; Pappas, Ashley L
Abstract: Purpose: The importance of a data management strategy is increasingly necessary for demonstrating value and driving performance within pharmacy departments. Data analytics capabilities often do not match the pace of data accumulation. At our organization, the establishment of an embedded pharmacy analytics and outcomes (PAO) team has been instrumental to pharmacy services in generating and demonstrating value and proactively supporting a business intelligence strategy grounded in a data-driven culture. Summary: The PAO team was established to support the operational and strategic needs of clinical, financial, and operational pharmacy services. The team is charged with implementing the vision of extending medication-use influence and data insight to drive value-based patient care outcomes while decreasing waste, optimizing therapeutic decisions, and achieving medication management standardization across the continuum of healthcare. The PAO team is composed of 3 pharmacist full-time equivalents (FTEs), 5 business analyst FTEs, 1 biostatistician FTE, 0.2 pharmacy intern FTE, and 1 pharmacy manager FTE. Pharmacy services leaders believe it is necessary to have a mix of both clinical and analytical skill sets, given the clinical nature of the data managed by team and complexities of the medication-use process. Conclusion: Pharmacy reporting and analytics should require the same depth of scrutiny and overview as any other step in the medication-use process where pharmacists are held accountable. For our organization, it was critical to establish pharmacist-level oversight into every portion of the analytics process where medication data are involved. This structure has led to measurable improvements in patient outcomes, operational efficiency, and financial performance.